A Street-Drug Elimination Initiative: The Law Enforcement Perspective - Di Luca, Kristen (Policing, 2010)
Purpose– The purpose of this study is to elucidate the elements, developmental stages, and operational steps of an open-air drug market intervention employed in two North Carolina communities in an effort to produce a model that can be duplicated by other law enforcement agencies. Design/methodology/approach– A systematic and practitioner-informed analysis of the steps and stages of the initiative is presented here. Law enforcement partners at the command and operational levels collectively contributed their voices to the synthesis of this model. Through purposive sampling, 13 key law enforcement stakeholders from the two police departments in North Carolina participated in semi-structured interviews conducted by a member of the research team. The interviews were transcribed and analyzed to extract participants' perceptions and recommendations regarding the intervention. Findings– Based on analyses of the interviews, the street-drug elimination strategy has been synthesized into several major steps. This paper elucidates the elements, developmental stages, and operational steps of the intervention. Research limitations/implications– This paper underscores important ingredients of the intervention and presents a model for other police departments to implement. Further examination of the strategy is necessary including research on improving the intervention, clarifying the factors that moderate the strategy's effectiveness, explicating the roles and perceptions of non-law enforcement partners and examining the continued impact of the initiative. Originality/value– The paper illustrates that this intervention has shown promise in reducing drug and violent crime associated with open-air drug markets and the research is of value to other police agencies that desire to implement this intervention